Analisis Tingkat Keramahan Lingkungan Alat Tangkap Pancing Ulur pada Penangkapan Gurita (Octopus sp) di Perairan Selatan Bali - Mega Tri Wahyuni; M. Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Denpasar is a major fisheries hub in Bali, with Benoa Harbor serving as a docking site for large fishing vessels. The decline in catch volume and annual production has increased the urgency of implementing environmentally friendly fishing and resource management practices. Fishers in Serangan continue to use handline fishing gear, prompting the need for research to assess its environmental friendliness. This study employed a survey method, collecting data through field observations, interviews, and questionnaires. The analysis was conducted based on nine criteria of the Code of Conduct for Responsible Fisheries (CCRF) with a sample of 30 respondents. The results show that handline fishing has high selectivity, targets octopus (Octopus sp) as the main catch, and has minimal impact on habitats and biodiversity. The lowest score was recorded in the criterion of minimum discarded catch due to the presence of bycatch such as skipjack tuna (Katsuwonus pelamis) and giant trevally (Caranx ignobilis), although these species still have market value. The total score obtained was 32.83, placing handline fishing in the highly environmentally friendly category.